(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
Society is dynamic and the law, in the same way, accompanies it. Under this premise, technologies are invented daily and offered by the most varied segments and it would be no different with the legal area. Artificial Intelligence is a specific branch of Information Technology that, applied to the field of law, brings numerous benefits, thus imperatively guaranteeing the achievement of fundamental rights and guarantees. Using AI in conflict resolution promises to bring significant benefits, but it also raises a number of important considerations that need to be addressed. Thus, the present work has, as its main objective, to investigate the applicability of Artificial Intelligence in the field of law and its logical ramifications. As an accessory, he analyzed the inflation of the Judiciary through the culture of judicialization in Brazil. Alternative means of conflict resolution in the country were presented, such as mediation, conciliation, negotiation and restorative justice. Artificial Intelligence and its overlap with the field of Judiciary were conceptualized, especially with regard to procedural management and automation of analysis of procedural themes and data. Alternative means of online conflict resolution and their synergy with Artificial Intelligence were exposed. It was concluded that the use and applicability of Artificial Intelligence as an alternative conflict resolution mechanism proves to be a capable instrument for deconcentrating the Judiciary and eradicating the culture of judicialization in the country. The research methodology was deductive, through the compilation of works on the subject in a qualitative and quantitative way through bibliographical research. Keywords: Artificial Intelligence; Judicial power; Alternative Means of Conflict Resolution.